Incidencia de episiotomía y factores de riesgo presentes en primigestas atendidas en el Hospital General Dr. Liborio Panchana Sotomayor durante el periodo enero - junio del 2024. - Alvarado Cerezo, Karla Zarela (2024)
The present research work focused on primigravidas who had natural births at the Dr. Liborio Panchana Sotomayor General Hospital during the period from January to June 2024, the objective was to determine the incidence of episiotomy and the main risk factors present in these patients, in order to understand the reasons behind carrying out this practice and how frequently it occurs. A quantitative, observational, analytical, descriptive and cross-sectional methodology was used for the study. The population was made up of 116 primigravidas who had their birth in the hospital, of which 89 patients were chosen to study using the finite population formula. The main hypothesis was that the most important risk factors for performing episiotomies in gilts are the average maternal age, the short stature of the mother, the gestational age, the prolonged duration of the expulsive period, the weight of the newborn and the perimeter cephalic. The data processing used to carry out the processing and analysis of the data of the research project, various computer tools were used. First of all, Microsoft Excel version 2019, which made it possible to perform statistical calculations, generate graphs and tables to manage the volume of information efficiently. The information database provided by the Dr. Liborio Panchana Sotomayor General Hospital was also used.